Peptide tyrosine tyrosine (PYY) as a new strategy for treating obesity - Ahmed Mostafa Mahmoud (Al-Azhar Assiut Medical Journal, 2016)
Background Obesity is a risk factor for obesity-related disorders such as type 2 diabetes mellitus, vascular disease, osteoarthritis, sleep apnea, and malignancy. Obesity cohinder the individual work capacity, and the cost for managing obesity complications is high. Objective The objective of this research was to study the role of pancreatic polypeptide family including neuropeptide Y and peptide tyrosine tyrosine (PYY) in obesity development and its metabolic changes. Materials and methods Twenty-seven adult female albino rats of a local strain were randomized into three equal groups for 5 weeks: sham-operated group, ovariectomized nontreated group, and ovariectomized treated group received PYY3–36 at a dose of 50 μg/kg, by intraperitoneal injection twice daily during the fifth week. Results Peripheral PYY3–36 administration reduces food intake, body weight gain, and serum glucose in ovariectomized obese female rats. Conclusion PYY system may offer a new therapeutic strategy for obesity management and its metabolic abnormalities.